2016
DOI: 10.1007/s13197-016-2385-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes and retention of vitamin E in reduced salt chicken sausages fortified with vitamin E

Abstract: The effect of salt reduction and vitamin E (a-tocopherol) fortification, at a level in excess of that required for a European Food Safety Authority (EFSA) health claim, on the quality of chicken sausages was investigated. Four formulations of chicken sausages were prepared: C (control, 1.3% NaCl, 0 mg/kg added a-tocopherol), L (low salt, 0.47% NaCl, 0 mg/kg added a-tocopherol), CE (1.3% NaCl, 200 mg/kg added a-tocopherol), LE (0.47% NaCl, 200 mg/ kg added a-tocopherol). Salt or a-tocopherol level did not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Microwaving (300 MHz, 2 min) fish has little effect on the stability of tocopherols (Polat and others ). In the case of meat, frying or grilling sausages does not affect the content of α ‐tocopherol (Bolger and others ), while grilling meat (beef, pork, and veal) reduces the content of vitamin E by 11% to 21.8% (Gerber and others ). No studies were found on the stability of vitamin K in cooked muscle tissue of meat and fish.…”
Section: Impact Of Cooking On the Nutritional Properties Of Meat And supporting
confidence: 91%
“…Microwaving (300 MHz, 2 min) fish has little effect on the stability of tocopherols (Polat and others ). In the case of meat, frying or grilling sausages does not affect the content of α ‐tocopherol (Bolger and others ), while grilling meat (beef, pork, and veal) reduces the content of vitamin E by 11% to 21.8% (Gerber and others ). No studies were found on the stability of vitamin K in cooked muscle tissue of meat and fish.…”
Section: Impact Of Cooking On the Nutritional Properties Of Meat And supporting
confidence: 91%
“…Phospholipase is an important enzyme that acts in both fat hydrolysis and flavor formation. e total phospholipase activities (Table 2) with DSE-0 were significantly increased from 0 to 15 h (P < 0.05), which could be due to the decrease of water activity and increase of salt content with prolonged processing time, and a certain amount of salt can promote the oxidation reaction [21]. e total phospholipase activities decreased significantly (P < 0.05) from 20 to 72 h, which might be attributed to the decrease in water activity because the salt content of sausage may not suitable for enzyme activities.…”
Section: Changes Of Total Phospholipase Activity In Cantonese Sausagementioning
confidence: 95%
“…One of the ways in which polyphenols work synergistically with other antioxidants is via the regeneration of α-tocopherol (Neunert et al 2015;Pazos et al 2007;Zhou et al 2005). Alpha-tocopherol is an effective antioxidant against lipid oxidation in meat (Bolger et al 2016). Notably, a strong synergistic effect between α-tocopherol and ferulic acid was observed in a liposome system.…”
Section: Regeneration Of Alpha-tocopherolmentioning
confidence: 99%